2014
DOI: 10.14319/ijcto.0204.14
|View full text |Cite
|
Sign up to set email alerts
|

A decision tool to adjust the prescribed dose after change in the dose calculation algorithm

Abstract: Purpose: This work aims to introduce a method to quantify and assess the differences in monitor unites MUs when changing to new dose calculation software that uses a different algorithm, and to evaluate the need and extent of adjustment of the prescribed dose to maintain the same clinical results. Methods: Doses were calculated using two classical algorithms based on the Pencil Beam Convolution PBC model, using 6 patients presenting lung cancers. For each patient, 3 treatment plans were generated: Plan 1 was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…It is interesting to note that the γ evaluation is not able to predict the change in the dose volume histogram either for the target volume or OAR. [24][25][26][27][28] Chaikh et al, 2014, showed for a specific patient, that 95% of pixels had γ < 1 with a γ average value less than unity 24 . In this case, we might conclude that there is no difference between the reference plan and the tested plan, but the real changes of dose distribution were not taken into consideration to protect the OAR.…”
Section: Limit Of Gamma Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…It is interesting to note that the γ evaluation is not able to predict the change in the dose volume histogram either for the target volume or OAR. [24][25][26][27][28] Chaikh et al, 2014, showed for a specific patient, that 95% of pixels had γ < 1 with a γ average value less than unity 24 . In this case, we might conclude that there is no difference between the reference plan and the tested plan, but the real changes of dose distribution were not taken into consideration to protect the OAR.…”
Section: Limit Of Gamma Evaluationmentioning
confidence: 99%
“…It was observed that a γ evaluation with (3%, 3 mm) under-estimated the dose in a small fraction of the target volume and overestimated the dose for OAR. 24 Zhen et al 2011, showed a significant correlation between 3D dose volumes in a patient geometry for QA comparison. 25 In this study, the dose difference reached up to 15%, while γ evaluation showed 95% of pixels as having γ < 1.…”
Section: Limit Of Gamma Evaluationmentioning
confidence: 99%